2023
DOI: 10.1002/adfm.202311622
|View full text |Cite
|
Sign up to set email alerts
|

Precise Synergistic Photothermal Therapy Guided by Accurate Temperature‐Dependent NIR‐II Fluorescence Imaging

Zhuqing Sun,
Tuanwei Li,
Feng Wu
et al.

Abstract: Photothermal therapy (PTT) is considered a promising treatment strategy for solid tumors. However, local hyperthermia (over 45°C) during PTT can cause severe side effects in neighboring healthy tissues. PTT with accurate temperature feedback is a compelling strategy to ablate tumors and reduce side effects, but it still faces challenges. Here, a new kind of phototheranostic nanoparticle, namely 17‐RF@Ag2Se is developed, enabling in vivo NIR‐II fluorescence tracking, PTT and fluorescence nanothermometry as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The mass of LSMPC-0.5 did not change within 7 days ( Supplementary Figure 1 ), indicating the non-degradability of LSMPC-0.5. We have reported that CSC degraded by 12% after 8 weeks, 36 which would provide space for new bone growth and osseointegration. Narrow facet interbody fusion devices currently used in minimally invasive interbody fusion are prone to interbody stress shielding, leading to vertebral collapse and fusion failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass of LSMPC-0.5 did not change within 7 days ( Supplementary Figure 1 ), indicating the non-degradability of LSMPC-0.5. We have reported that CSC degraded by 12% after 8 weeks, 36 which would provide space for new bone growth and osseointegration. Narrow facet interbody fusion devices currently used in minimally invasive interbody fusion are prone to interbody stress shielding, leading to vertebral collapse and fusion failure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research reported that it can cause damage to tissues when the temperature is over 45 °C for a long period. 36 Although the transformation temperature of the prepared LSMPC is about 45 °C, the shape recovery can be completed within 5 minutes, indicating limited thermal damage to human tissues.
Figure 7 Feasibility of spinal fusion device.
…”
Section: Resultsmentioning
confidence: 99%